Affective and Cognitive Empathy in Pre-teachers With Strong or Weak Professional Identity: An ERP Study - Zhu, Juncheng; Wang, Xin Qiang; He, Xiaoxin; Hu, Yuan-Yan; Li, Fuhong; Liu, Ming-Fan; Ye, Baojuan (Frontiers in Human Neuroscience, 2019)
Pain empathy is influenced by a number of factors. However, few studies have examined the effects of strength of professional identity on pain empathy in pre-service teachers. This study used the event-related potential (ERP) technique, which offers a high temporal resolution, to investigate the neurocognitive mechanisms of pain empathy in pre-teachers with strong or weak professional identity. The N110 and P300 components have been shown to reflect an individual’s emotional sharing and cognitive evaluation in pain empathy, respectively. The results of the current study show that pre-teachers with strong professional identity showed a significant difference in N110 amplitudes evoked towards painful and non-painful stimuli; whereas pre-teachers with weak professional identity did not show a significant difference in the amplitudes evoked by the two stimulus types. For the P300 component, pre-teachers with weak professional identity showed a significant difference in the amplitudes evoked towards painful and non-painful stimuli; whereas pre-teachers with strong professional identity did not show a significant difference in the amplitudes evoked by the two stimulus types. Our results indicate that pre-teachers with strong professional identity show a higher level of pain empathy than those with weak professional identity.